Green tea epigallocatechin-3-gallate inhibits angiogenesis and suppresses vascular endothelial growth factor C/vascular endothelial growth factor receptor 2 expression and signaling in experimental endometriosis in vivo. - Xu, H; Becker, C; Lui, W; Chu, C; Davis, T; Kung, A; Birsner, A; D'Amato, R; Man, W; Wang, C (2011)
OBJECTIVE: To investigate the antiangiogenesis mechanism of epigallocatechin-3-gallate (EGCG) in an endometriosis model in vivo. DESIGN: Animal studies. SETTING: University laboratory. ANIMAL(S): Human endometrium from women with endometriosis (n = 10) was transplanted into immunocompromised mice. INTERVENTION(S): Mice (n = 30) were randomly treated with EGCG, vitamin E (antioxidant control), or vehicle (negative control) for microvessel imaging. MAIN OUTCOME MEASURE(S): Endometriotic implants were collected for angiogenesis microarray and pathway analysis. Differentially expressed angiogenesis molecules were confirmed by quantitative polymerase chain reaction, Western blot, and immunohistochemistry. Effects of EGCG on angiogenesis signal transduction were further characterized in a human endothelial cell line. Microvessel parameters and the angiogenesis signaling pathway in endometriotic implants and endothelial cells were studied. RESULT(S): EGCG, but not vitamin E, inhibited microvessels in endometriotic implants. EGCG selectively suppressed vascular endothelial growth factor C (VEGFC) and tyrosine kinase receptor VEGF receptor 2 (VEGFR2) expression. EGCG down-regulated VEGFC/VEGFR2 signaling through c-JUN, interferon-γ, matrix metalloproteinase 9, and chemokine (C-X-C motif) ligand 3 pathways for endothelial proliferation, inflammatory response, and mobility. EGCG also suppressed VEGFC expression and reduced VEGFR2 and ERK activation in endothelial cells. VEGFC supplementation attenuated the inhibitory effects by EGCG. CONCLUSION(S): EGCG inhibited angiogenesis and suppressed VEGFC/VEGFR2 expression and signaling pathway in experimental endometriosis in vivo and endothelial cells in vitro.